2005
DOI: 10.1002/jnr.20602
|View full text |Cite
|
Sign up to set email alerts
|

Variations in extracellular levels of dopamine, noradrenaline, glutamate, and aspartate across the sleep–wake cycle in the medial prefrontal cortex and nucleus accumbens of freely moving rats

Abstract: We used intracerebral microdialysis coupled with electrophysiologic recordings to determine relative changes in the concentrations of several neurotransmitters in the medial prefrontal cortex and nucleus accumbens of freely moving rats during waking, slow-wave sleep, and rapid eye movement (REM) sleep. The concentrations of noradrenaline, dopamine, glutamate, and aspartate in 2-min dialysate samples were analyzed by capillary electrophoresis combined with laser-induced fluorescence detection. Changes in glutam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
171
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(199 citation statements)
references
References 45 publications
26
171
0
2
Order By: Relevance
“…Thus, we propose that REM sleep neural pathways are only activated when D 2 dopamine receptors are activated on a background of reduced mesolimbic glutamatergic and serotonergic tone. Importantly, this is consistent with neurotransmitters levels observed during REM sleep (Trulson and Jacobs, 1979;Park et al, 1999;Lena et al, 2005), and during the waking period of DAT-KO mice immediately after exposure to novelty (Gainetdinov et al, 1999(Gainetdinov et al, , 2001). This also predicts that psychosis may be generated by pharmacological agents that activate the D 2 dopamine receptor while altering specific aspects of glutamatergic or serotonergic transmission (Kapur and Seeman, 2002;Seeman et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Thus, we propose that REM sleep neural pathways are only activated when D 2 dopamine receptors are activated on a background of reduced mesolimbic glutamatergic and serotonergic tone. Importantly, this is consistent with neurotransmitters levels observed during REM sleep (Trulson and Jacobs, 1979;Park et al, 1999;Lena et al, 2005), and during the waking period of DAT-KO mice immediately after exposure to novelty (Gainetdinov et al, 1999(Gainetdinov et al, , 2001). This also predicts that psychosis may be generated by pharmacological agents that activate the D 2 dopamine receptor while altering specific aspects of glutamatergic or serotonergic transmission (Kapur and Seeman, 2002;Seeman et al, 2005).…”
Section: Discussionsupporting
confidence: 84%
“…REM is characterized by prominent hippocampal theta oscillations (Vanderwolf, 1969;Timo-Iaria et al, 1970;Cantero et al, 2003) that are highly correlated with dreaming (Aserinsky and Kleitman, 1953;Dement and Kleitman, 1957a,b;Jouvet et al, 1959). Furthermore, recent evidence suggests that REM is also characterized by an increase in mesolimbic dopamine release (Lena et al, 2005). This is consistent with our results, which demonstrate that the pathological REM-like hippocampal theta oscillations are modulated by antipsychotic and psychotomimetic agents that alter dopaminergic transmission.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The 5-HT2A receptor indirectly controls glutamatergic signaling. Furthermore, slow wave sleep and REM sleep are generally associated with decreased glutamate levels (58), and antagonism of NMDA receptors increases delta power in NREM sleep in rats (59). With regard to the functional consequences of these regulatory processes, we found that sleep deprivation led to an increase in the 5-HT2Areceptors.…”
Section: Discussionmentioning
confidence: 74%
“…Dopamine (DA) has been identified as a key substance in the regulation of sleep-wake states (1)(2)(3)(4)(5)(6)(7). DA is critically involved in regulating complex movements and emotions (8).…”
Section: Introductionmentioning
confidence: 99%